2019
DOI: 10.1016/j.ienj.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Emergency clinician perceptions of occupational stressors and coping strategies: A multi-site study

Abstract: Background: Research exploring multi-disciplinary emergency department (ED) clinicians' perceptions of their working environment is limited, although exposure to occupational stressors is frequent. This study describes ED clinicians' perceptions of their working environment, occupational stressors and their use of coping strategies. Methods: A cross-sectional descriptive study was conducted in 2017 at two Australian public hospital EDs. Nursing and medical staff completed a print-based survey of 100 items, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 36 publications
1
31
0
3
Order By: Relevance
“…Emergency departments (EDs) are experiencing increasing service demands [15,16], which can lead to increased workload and pressures on ED nursing personnel [17]. Moreover, in ED, waiting times, a demanding public, overcrowding, and inadequate human resources are common stressors [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency departments (EDs) are experiencing increasing service demands [15,16], which can lead to increased workload and pressures on ED nursing personnel [17]. Moreover, in ED, waiting times, a demanding public, overcrowding, and inadequate human resources are common stressors [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Emergency departments (EDs) are experiencing increasing service demands [15,16], which can lead to increased workload and pressures on ED nursing personnel [17]. Moreover, in ED, waiting times, a demanding public, overcrowding, and inadequate human resources are common stressors [17,18]. Similarly, occupational stress, defined as the perception of a discrepancy between environmental demands (stressors) and individual capacities to fill these demands determined by work organization, work design, and labor relations [19], is also associated with burnout [20].…”
Section: Introductionmentioning
confidence: 99%
“…First, using a modified NGT, all the clinicians who agreed to participate were emailed a link to a survey, to identify the stressor they felt was most important to address. The stressors contained in the survey were derived from triangulation and integration of previously collected quantitative and qualitative data 11–12 . The second part of the data collection process was conducted through two separate face‐to‐face consensus NGT sessions with two different groups of participants 9 .…”
Section: Methodsmentioning
confidence: 99%
“…As such, the relationship between JCS subscales, the WES-10 subscales and the EDSS were examined. For the EDSS, we focussed on the five stressors that are most commonly reported in the ED: heavy workload, environmental concerns (eg, overcrowding), inability to provide optimal care, high acuity patients and workplace violence 28 29. Scatter plots showed that all associations were linear with no influential outliers.…”
Section: Methodsmentioning
confidence: 99%